MODERN APPROACHES TO THE FABRICATION OF COMPLETE DENTURES (Ideal Journal of Multidisciplinary Research, 2026)
Complete dentures remain one of the primary treatment options for edentulous patients despite advances in implant dentistry. Modern prosthodontics has significantly evolved through digital technologies, improved materials, and patient-centered treatment concepts. The aim of this study was to analyze contemporary approaches to complete denture fabrication based on current scientific literature. A narrative literature review was conducted using publications from 2015–2025 indexed in PubMed and Google Scholar. The findings demonstrate that digital workflows, CAD/CAM manufacturing, and improved impression techniques enhance accuracy, reduce clinical visits, and improve patient satisfaction. However, conventional methods remain relevant in specific clinical situations. The integration of digital and traditional techniques represents the current trend in prosthodontics.
Keywords: complete dentures, CAD/CAM dentistry, digital prosthodontics, edentulism, removable prostheses.